PEMBUATAN APLIKASI PUBLIC SERVICE ADMINISTRATION BERBASIS WEB PADA KANTOR KECAMATAN PRABUMULIH SELATAN - Clara Mariska Mardianto; Andi Christian; Rishi Suparianto (Elkom: Jurnal Elektronika dan Komputer, 2023)
Public services in several districts have not utilized online information and communication technology. So that the service applicant has to go back and forth to the sub-district which takes a very long time. For this reason, with the development of the modern era, employees should provide good service to the community, such as running community service programs using applications. This research aims to create Community Public Service Application programs and to help people carry out services using Web-based Public Service Administration service applications in South Prabumulih District. This research uses descriptive research type. The type of data taken is quantitative data. Sources of data in this study using primary data sources and secondary data sources. Data collection techniques in this study were carried out by observation, interviews and literature studies. The system development method used in this research is the Water Fall Method, and the System Design Auxiliary Tool.